Analysis of acoustic environment on premises of nursery schools in Wrocław - Barbara RUDNO-RUDZIŃSKA; Karolina CZAJKOWSKA (Archives of Acoustics, 2013)
The aim of this project was to create a ranking of the nursery schools in Wrocław with regard to the quality of the acoustic environment on their premises, using a specially developed evaluation methodology. Each nursery school was rated according to an adopted grading scale on the basis of the noise level distribution on the playground and on the nursery school building facades. Using the grading scale one can classify nursery school premises into twelve categories characterized by different acoustic environment quality, from exceptionally good (< 45 dB) to exceptionally bad (> 70 dB). The appropriately rescaled data from the acoustic map of Wrocław and the authors' own measurements and simulation analyses were used. The developed methodology was verified by comparing the ratings yielded by it with those determined on the basis of field measurements and simulation studies, carried out for several selected nursery schools. The paper presents the results of an acoustic environment quality assessment carried out, using the developed investigative methodology, for 118 nursery schools located in Wrocław.